Nursing consultation tool for people with human immunodeficiency virus/tuberculosis co-infection - Alexsandra Rodrigues Feijão; Gilmara Holanda Cunha; Joselany Áfio Caetano; Elucir Gir; Marli Teresinha Gimeniz Galvão (Rev Rene)
Objective: to verify the opinion of judges about a nursing consultation tool for people with co-infection by the human immunodeficiency virus and tuberculosis. Methods: methodological study, involving the construction of a tool based on Orem’s self-care theory and its submission for evaluation by judges experts in the area, which gave opinions about organization, clarity and relevance. Results: the instrument gained a positive evaluation for all assessment criteria, with agreement greater than 75% and Content Validity Index greater than 0.80 in most items. Following judges opinion, three items were excluded and two modified. Conclusion: the adequacy of the nursing consultation tool for people with HIV/tuberculosis co-infection was confirmed regarding organization into subdivisions and items. Minimal disagreement among judges in the analysis of the issues was noted. Although most items were evaluated positively, further validation studies will be needed.